Very Messy Adventure - Tuma, Refe; Tuma, Susan (New York Boston Little, Brown and Company, 2015)
Photographs and simple text reveal the mischief toy dinosaurs get into all night long, from knocking over potted plants to painting on walls.
LC copy signed by author.
Accelerated Reader AR
113605
Keywords: Dinosaurs -- Juvenile fiction; Toys -- Juvenile fiction; Conduct of life -- Juvenile fiction; Humorous stories; Behavior -- Fiction; Juvenile Fiction -- Animals -- Dinosaurs & Prehistoric Creatures; Juvenile Fiction -- Toys, Dolls & Puppets; Humorous stories; Be ready rover; novels